2009
DOI: 10.1007/s00484-009-0291-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season on sleep and skin temperature in the elderly

Abstract: The effects of season on sleep and skin temperature (Tsk) in 19 healthy, elderly volunteers were investigated. Measurements were obtained in summer, winter, and fall, and activity levels were monitored using a wrist actigraph system for five consecutive days. The temperature and humidity of the bedrooms of the subjects' homes were measured continuously for five days. During actigraphic measurement, Tsk during sleep was measured for two nights. The bedroom temperature and humidity significantly increased in sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 51 publications
5
44
2
Order By: Relevance
“…A recent paper by Okamoto-Mizuno and Tsuzuki (2009) reported the seasonal variation of sleep in the elderly over 61 years old in relation to skin temperature. They monitored sleep by using a wrist accelerometer system for five consecutive days.…”
mentioning
confidence: 99%
“…A recent paper by Okamoto-Mizuno and Tsuzuki (2009) reported the seasonal variation of sleep in the elderly over 61 years old in relation to skin temperature. They monitored sleep by using a wrist accelerometer system for five consecutive days.…”
mentioning
confidence: 99%
“…Finally, the finding that higher evening indoor temperature was associated with shorter SOL was for cold seasons only. However, a study comparing sleep quality among the four seasons found that the worst sleep quality was in summer [29]. Further study including all seasons is necessary to determine the optimal indoor temperature for sleep.…”
Section: Discussionmentioning
confidence: 95%
“…These experimental studies conducted under controlled conditions in terms of posture, physical activity, clothing, and temperature suggest an association between the thermal environment and SOL. However, the impact of evening indoor temperature on SOL in real life situations remains unclear because there are many Physiology & Behavior 149 (2015) [29][30][31][32][33][34] factors that could modify the association, such as habitual bedtime, physical activity, time spent outdoors, posture, and clothing.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, thermophysiological effect of humidity on sleep has been reported in terms of a number of body temperature indices (Okamoto-Mizuno et al 1999, 2003Okamoto-Mizuno et al 2005a, 2005bBuguet 2007;Tsuzuki et al 2008;Okamoto-Mizuno and Tsuzuki 2010). A number of hypotheses have been proposed to explain the sleep structure regulation of which four have been discussed.…”
Section: Introductionmentioning
confidence: 94%
“…(1) mechanistic characterization of sleep and humidity interaction (2) development of sleep management strategies through feasible modulation of human thermal comfort factors High humid heat condition has deleterious effect on sleep parameters with increasing effect on stage Wake, WASO (wake after sleep onset), sleep latency, stage 1 and decreasing effect on SWS (slow wave sleep), stage 3, REM (rapid eye movement), TST (total sleep time) and SEI (sleep efficiency index) (OkamotoMizuno et al 1999(OkamotoMizuno et al , 2003Okamoto-Mizuno et al 2005a, 2005bBuguet 2007;Tsuzuki et al 2008;Okamoto-Mizuno and Tsuzuki 2010) . Similarly, thermophysiological effect of humidity on sleep has been reported in terms of a number of body temperature indices (Okamoto-Mizuno et al 1999, 2003Okamoto-Mizuno et al 2005a, 2005bBuguet 2007;Tsuzuki et al 2008;Okamoto-Mizuno and Tsuzuki 2010).…”
Section: Introductionmentioning
confidence: 98%